Expressive Illocutionary Acts Found in “Kung Fu Panda 4” Movie - Ida Bagus Yudi Wardana; I Gede Agoes Caskara Surya Putra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The goal of the study is to contribute to the solution of research problems by identifying the issues with expressive speech acts through an analysis of emotional expression, relationship building, and self-identity. Particularly in this study that uses data from the Kung Fu Panda 4 movie, to differentiate between the various types of expressive illocutionary acts in the film, this study used a descriptive qualitative method, with data analysis based on Yule's (1996) theory. Six expressive types are identified by this study in films: doubting, anger, praise, joy, blaming, and regretting. 24 doubting, 21 angry, 17 praising, 13 joy, 12 blaming, and 9 regretting were among the 96 examples that were discovered. This study reveals important details about the expressive personalities in the movie in addition to speech act types.